(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2012)
Trimetazidine is an effective and well-tolerated antianginal drug. In the present study, a simple, sensitive and specific liquid chromatography (HPLC) method with UV detection was developed and validated for the quantification of trimetazidine in human serum samples using caffeine as internal standard. Protein precipitation method with methanol was employed in the extraction of trimetazidine and caffeine from biological matrix. The chromatographic separation was accomplished on Xterra C18 Column with a mobile phase consisting 0.01 M potassium dihydrogen phosphate buffer (pH 4.16 ± 0.01 adjusted with orthophosphoric acid, with a solvent system of triethanolamine and acetonitrile (90:10) at a flow rate of 1.0 ml/min. The chromatogram was monitored at a wavelength of 207 nm. The method was validated over a linear concentration range of 5-200 ng/ml and limit of quantification (LOQ) was 5.0 ng/ml with a coefficient of correlation (r2) ? 0.996. The intra-day and inter-day precision expressed as relative standard deviation was 3.40%-11.63% and 1.30%-10.21%, respectively. The average recovery of trimetazidine from serum was 97.44%. The method was successfully applied to a pharmacokinetic study after oral administration of modified release trimetazidine hydrochloride tablet (35 mg) in healthy Bangladeshi volunteers. DOI: http://dx.doi.org/10.3329/dujps.v10i2.11783 Dhaka Univ. J. Pharm. Sci. 10(2): 71-78, 2011 (December)